Different Nodules Identified during Liver Explant Gross Examination: Relevance and Need for Sectioning—Experience from India - Nalini Bansal; Vivek Vij; Mukul Rastogi (International Journal of Hepatology)
Objective. The goal of this study was to determine the etiopathological association of various hepatic nodules identified during gross examination of liver explants specimen and the grossing aspects of these abnormal nodules especially those smaller than 1 cm in diameter. Our aim was to analyze whether there is any association of macroregenerative and dysplastic nodule with hepatocellular carcinoma. Materials and Methods. Fifty consecutive liver explants specimens were analyzed for the presence of any abnormal nodule (abnormal nodule defined as any nodule different in color, texture, and appearance from adjacent liver tissue). Results. Of the total 40 abnormal nodules identified in 50 liver explant specimens, there were 12 (30%) HCC [including 5 small HCC (41% of total HCC) and 1 steatohepatitic HCC (8% of total HCC)], 11 (27%) MRNs, 8 (20%) dysplastic nodules, and 9 (22%) necrotic nodules. Most cases (72%) of MRN are seen in hepatitis C virus related cirrhosis with only 2 cases having associated HCC. Most cases of HCC were seen in cases of HBV associated cirrhosis (60%). The association of MRN was not found to be significantly associated with HCC with a p value of 1.0. Dysplastic nodules were found to be significantly associated with HCC with a p value of 0.02. Conclusion. In hepatic carcinogenesis, the role of MRN does not appear to be significant. However, the presence of dysplastic nodules is significantly associated with HCC. The study identified another variant of cirrhotic nodules herein called necrotic nodules that are mostly tan greenish in color and <0.5 cm in diameter. No dysplastic changes were identified in any of these nodules disqualifying the need of sectioning in such nodules.